IDENTIFICATION OF KEY FACTORS TO IMPROVE NURSES' TRIAGE COMPETENCE IN HOSPITALS: A SCOPING REVIEW - Angga Andreas Wantoro (Nurse and Health)
Background: Many emergency department nurses still lack adequate competency in performing triage, so hospital management needs to understand the right strategies to enhance triage competencies. Objective: The purpose of this scoping review is to identify and analyze the essential factors contributing to the improvement of nurses' triage competencies in hospitals. Methods: This scoping review was conducted by identifying scientific articles in five databases: ScienceDirect, ProQuest, Google Scholar, Wiley Online Library, and Springer Link. The authors used the keywords "emergency nurses" AND "triage competency" AND "emergency department." After identification, the authors selected and analyzed articles using PRISMA based on predefined inclusion and exclusion criteria. Studies obtained from various databases yielded 186 research articles, and from this number, 10 relevant articles were extracted for data analysis. Results: Ten studies were included in this scoping review, and the most important factor in improving triage competency was participating in triage training, providing innovative triage learning methods, and developing nurses' professional self-concept. This review shows that the most effective effort is to provide triage training, as it covers all triage related material in depth by applying various learning methods aligned with actual practice. Conclusion: This review found that triage training is the most effective factor in improving nurses' triage competency in hospitals.